algebra

posted by .

What is the solution of the system?
Solve the system of equations using the substitution method.
x-y=-1
5x+4y=-23

• algebra -

Eqn (1) to be mly by 4,
then we have 4x-4y=-4,
(2)5x+4y=-23
----------
9x+ 0=-27
9x=-27
x=-27/9=-3
x=-3.
to get y,
we substitute in the eqn(1)
(x-y=-1) as -3-y=-1
-3+1=y
y=-2.

Therefore, we get x=-3
y=-2

Similar Questions

2. algebra

when you solve a system of equations by the substitution method, how do you determine whether the system of equations is dependent?
3. algebra

i need help with these problems (either a solution or how to plug them into a graphing calculator): 1) Solve by substitution or elimination 4/x + 1/y + 2/z = 4 2/x + 3/y - 1/z = 1 1/x + 1/y + 1/z = 4 2)Solve the system of equations …
4. algebra

Can someone please help. When you solve a system of equations by the substitution method, how do you determine whether the system of equations is inconsistent?
5. algebra

Can someone help me figure this out please?
6. algebra

When you solve a system of equations by the substitution method, how do you determine whether the system of equations is inconsistent?
7. Algebra

I can find no solution to this system of equations. Solve the system of equations using the substitution method 2x + 4y = -2 2x - y = 4
8. Algebra 1

solve the system of equations using the substitution method. 8x-9=y, y-8x=-4
9. algebra

solve the system of equations using the substitution method 8x - 9 = y, y - 8x = 4
10. algebra

solve the system of equations using the substitution method 8x - 9 = y y - 8x = -4

More Similar Questions